#TITLE_ALTERNATIVE# - AHNAF FAQIH SHAIMY (NIM. 101 07 059); Pembimbing Tugas Akhir : Dr. Agus Yodi Gunawan, RADEN
A hydrodynamic stability problem often leads to an equation of eigenvalue problem. There are some simple equations to be solved but most are difficult ones. The Chebyshev-T method is one method that can be used to solve various eigen value problems arising from hydrodynamic stability studies. The method applies Chebyshev-T polynomials to approximate the solution. This final project describes the process of applying Chebyshev-T method to find all the eigenvalues that can appear in hydrodynamic stability equation. Especially, application of the method to the equations that have a second (and fourth) order of ordinary differential equation (ODE) is presented. Our illustration can then be considered as a benchmark for solving more complex hydrodynamic stability problems.